Compassionate Use of Yuanjiang Decoction, a Traditional Chinese Medicinal Prescription, for Symptomatic Bradyarrhythmia - Wan-Tong, Zhang; Bao-Chen, Zhu; Zhao, Liu; Xu-Jie, Wang; Rui, Gao; Ning, Xiao; Wei, Tang; Yu-Fei, Wu; Miles, Phoebe; Wei-Liang, Weng; Hao-Xiang, Lin; Qiu-Yan, Li (Frontiers in Pharmacology, 2022)
Background: No effective medication is available for symptomatic bradyarrhythmia, particularly in low socioeconomic status (SES) population. Objective: To explore the safety and efficacy of Yuanjiang decoction, a traditional Chinese medicinal prescription, for symptomatic bradyarrhythmia on a compassionate-use basis. Methods: This compassionate-use study was conducted in Beijing, China between January 2019 and January 2020. Eligible participants were recruited and treated with Yuanjiang decoction (composed of 6 Chinese herbal medicines), 200 mL twice daily for 16 weeks. Analyses were done with the intention-to-treat (ITT) approach. The primary outcome measure was the proportion of participants who achieved a favorable treatment outcome at 16 weeks. Results: As of January 2020, 184 patients were included. After 16-weeks treatment, 12 participants were lost to contact while 21 participants were terminated from this study, with a drop-out rate of 17.93%. The most common treatment-related adverse events were xerostomia (6.52%), constipation (6.45%) and sleepiness (3.26%). The proportion of participants with favorable treatment outcome was 65.22% at 4 weeks, 59.78% at 8 weeks (OR: 1.11, 95% CI: 0.71-1.73), 61.41% at 12 weeks (OR: 1.16, 95% CI: 0.92-1.45) and 60.87% at 16 weeks (OR: 1.15, 95% CI: 0.98-1.35). In the multifactor regression analysis, the favorable treatment outcome at 16 weeks was significantly associated with completing at least 8 weeks treatment (OR: 2.053, 95% CI: 1.064-3.560), while unfavorable treatment outcome was significantly associated with an atrioventricular block (OR: 0.255, 95% CI: 0.083-0.784), current smoking (OR: 0.343, 95% CI: 0.027-0.487), and syncope in the month before treatment (OR: 0.321, 95%CI: 0.114-0.904). Conclusions: This compassionate-use study showed encouraging outcomes of treatment with Yuanjiang decoction, without serious adverse events. This study identified several key factors that may affect outcomes. These findings helped inform the design and assess the feasibility of a large-scale randomized clinical trial.